Synthesis, characterization and application of magnetic carbon materials as electron shuttles for the biological and chemical reduction of the azo dye Acid Orange 10 - Pereira, Luciana (2017)
Supplementary data associated with this article can be found,in the online version, at http://dx.doi.org/10.1016/j.apcatb.2017.04.060.